Upaya Meningkatkan Kinerja Guru Melalui Supervisi Akademik di MTsN 3 Kota Padang Tahun Pelajaran 2022/2023 - Nurhidayati, Nurhidayati (Science and Education Journal (SICEDU), 2023)
This research is a school Action Research which aims to find out whether there is an increase in teacher performance at MTsN 3 Kota Padang in the 2022/2023 academic year after the implementation of supervisory activities by the head of the madrasa. The background for this school's action research was in the context of improving teacher performance, where teacher performance was still unsatisfactory. The purpose of this study was to obtain information about efforts to improve teacher performance at MTsN 3 Kota Padang. This research is a school action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 6 teachers at MTsN 3 Kota Padang. This research was conducted in the odd semester of the 2022/2023 school year. Research data was collected using observation sheets. Data were analyzed using percentages. The results of the study show that academic supervision can improve teacher performance at MTsN 3 Kota Padang. As seen in the first cycle the average quality of teacher performance is 53 in the Enough category while in the second cycle the quality of teacher performance is 86 in the Very good category.